Pengaruh Earning Per Share, Struktur Modal dan Return On Assets Terhadap Harga Saham Pada Perusahaan Subsektor Perdagangan Besar dan Perdagangan Kecil Yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020 - Anastasia Tetriani; Latersia Br Gurusinga (Jurnal Akuntansi dan Pajak, 2022)
This study aims to examine and analyze the effect of earnings per share, capital structure and return on assets on stock prices in large and small trading sub-sector companies listed on the Indonesia stock exchange for the 2016-2020 period. The research method used in this study uses quantitative research methods with quantitative descriptive research that is explanatory research. The population of this research is all large trading and small trading sub-sector companies listed on the Indonesia Stock Exchange totaling 61 companies. The sample of this research is 15 companies with purposive sampling technique. The results of the study show that partially Earning Pershare has an effect on stock prices, the rest Capital Structure and Return On Assets have no effect on Stock Prices. Simultaneously Earning Per Share, Capital Structure and Return On Assets affect earnings per share Keywords: Earning Per Share, Capital Structure and Return On Assets, Stock Price